Interdigital structures of heavy ions linear accelerators: their tuning, beams focusing and use (review) - Dyachenko, О.F. (Вопросы атомной науки и техники, 2019)
The review interdigital H-accelerating structures (IHAS) of the heavy ions linear accelerators developed in NSC KIPT throughout several tens of years is presented. It is shown that in structures with individual stems all kinds of focusings are applicable: quadrupole, grid, alternating-phase (APF, in various variants), high-frequency (in various variants) and their combinations. Corresponding constructive decisions are developed for accelerating structures of different function. Essentially new approaches for their adjustment for the set distribution of an accelerating field and frequency (by countering corner change) and some new regulating elements are offered: the end resonant elements of adjustment (EREA) and inductance-capacitor elements (сontrivances). By results of modelling three real accelerating sections which are created at modernization of the multicharge ions linear accelerator were developed. New variants pre-stripping area of the heavy ions accelerator with the relation of mass number to charge A/q = 20 are offered.